2004
DOI: 10.1038/sj.eye.6701755
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular pressure during haemodialysis: a review

Abstract: Objectives Although several works in the past have examined the effect of haemodialysis (HD) on intraocular pressure (IOP), reported findings, theories, and conclusions are very different. The objectives of this article are to resume the reported evidence of IOP changes during HD, to review the proposed hypothesis of HD influence on IOP, and to determine if ophthalmic examination is imperative in HD patients. Methods We analysed the peer-reviewed English literature and selected all possible relevant articles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 29 publications
0
47
1
1
Order By: Relevance
“…Results of published studies based on the effects of HD on IOP change can be classified into three groups [7]: reports showing IOP rise [4,[14][15][16][17][18], reports showing IOP decrease [19,20], and reports showing no significant change in IOP [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of published studies based on the effects of HD on IOP change can be classified into three groups [7]: reports showing IOP rise [4,[14][15][16][17][18], reports showing IOP decrease [19,20], and reports showing no significant change in IOP [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…In view of the fact that conflicting results have been reported concerning the effects of HD on IOP, the exact outcomes of HD on IOP are still not clear [7]. Osmotically active substances are eliminated by diffusion during HD, resulting in loss of body fluids and decrease in blood osmolality [8].…”
Section: Introductionmentioning
confidence: 99%
“…This may be attributed to the methodological differences, such as different exclusion criteria, variable sample size and different tonometry techniques and possibly due to significant technical progress in the HD procedure itself over the years [28]. There are several studies, which demonstrate an elevation of IOP during an HD session [6][7][8][9][10][11][12][13][14][15].…”
Section: Association Of Iop and Hd-clinical Studiesmentioning
confidence: 99%
“…Some IOP readings were performed before and after HD, while others every 30 min, hourly, every 2 h or 2 h after the commencement of the HD session. Therefore, whether the conflicting results are due to different HD techniques or to discrepancies in IOP measurement techniques employed by the various authors remains as yet unclear [28]. Intraocular pressure is measured by various techniques (Goldmann, Perkins, Schiotz, pneumotonometer, air tonometer).…”
Section: Association Of Iop and Hd-clinical Studiesmentioning
confidence: 99%
“…A systematic review concluded that the relationship was not clear. 1 Reports of IOP rise during HD in neovascular 2,3 and pseudo-exfoliative glaucoma are extremely limited. 4,5 Mechanisms for elevated IOP during HD are unclear; some authors propose that reduced plasma osmolality causes increased aqueous humour production and potential to elevate IOP.…”
Section: Commentmentioning
confidence: 99%